Design and synthesis of small molecule-sulfotyrosine mimetics that inhibit HIV-1 entry. Issue 8 (15th April 2016) - Dogo-Isonagie, Cajetan; Lee, Su-Lin; Lohith, Katheryn; Liu, Hongbing; Mandadapu, Sivakoteswara R.; Lusvarghi, Sabrina; O'Connor, Robert D.; Bewley, Carole A.
Graphical abstract: Abstract: In the absence of a cure or vaccine for HIV/AIDS, small molecule inhibitors remain an attractive choice for antiviral therapeutics. Recent structural and functional studies of the HIV-1 surface envelope glycoprotein gp120 have revealed sites of vulnerability that can be targeted by small molecule and peptide inhibitors, thereby inhibiting HIV-1 infection. Here we describe a series of small molecule entry inhibitors that were designed to mimic the sulfated N-terminal peptide of the HIV-1 coreceptor CCR5. From a panel of hydrazonothiazolyl pyrazolinones, we demonstrate that compounds containing naphthyl di- and tri-sulfonic acids inhibit HIV-1 infection in single round infectivity assays with the disulfonic acids being the most potent. Molecular docking supports the observed structure activity relationship, and SPR confirmed binding to gp120. In infectivity assays treatment with a representative naphthyl disulfonate and a disulfated CCR5 N-terminus peptide results in competitive inhibition, with combination indices >2. In total this work shows that gp120 and HIV-1 infection can be inhibited by small molecules that mimic the function of, and are competitive with the natural sulfated CCR5 N-terminus.